AMP-Activated Protein Kinase Activation by 5-Aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR) Inhibits Palmitate-Induced Endothelial Cell Apoptosis Through Reactive Oxygen Species Suppression - Ji-Eun Kim; Yong-Woon Kim; In Kyu Lee; Jong-Yeon Kim; Young Jin Kang; So-Young Park (Journal of Pharmacological Sciences, 2008)
AMP-activated protein kinase (AMPK) activation has an antiapoptotic effect in endothelial cells, but the mechanisms involved remain unclear. Here, we investigated whether AMPK activation could inhibit palmitate-induced apoptosis through suppression of reactive oxygen species (ROS) production in bovine aortic endothelial cells. Palmitate increases ROS generation and thereby p38 activation, which leads to apoptosis in bovine aortic endothelial cells. The AMPK activator 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR) and constitutive active AMPK inhibit palmitate-induced apoptosis through suppression of ROS. The AMPK inhibitor compound C, dominant-negative AMPK, and the uncoupling protein inhibitor guanosine diphosphate block the antiapoptotic and antioxidative effects of AICAR. The increase in uncoupling protein 2 (UCP2) by AICAR is also suppressed by compound C and guanosine diphosphate. AICAR-mediated suppression of palmitate-induced p38 activation is also inhibited by guanosine diphosphate. Over-expression of UCP2 inhibits palmitate-induced apoptosis and ROS generation. These data suggest that the activation of AMPK inhibits palmitate-induced endothelial cell apoptosis through the suppression of ROS generation, and UCP-2 may be one of possible mediators of the antioxidative effect of AMPK. Keywords:: apoptosis, endothelial cell, palmitate, AMP-activated protein kinase (AMPK), reactive oxygen species (ROS)